Pemberian Static Bicycle dan Quadriceps Strengthening Exercise pada Pasien Post TKR Dextra et causa Osteoarthritis Knee Bilateral di RST dr. Soedjono Magelang: Studi Kasus - Rona Fariza; Dwi Rosella Komala Sari; Munawar Munawar (Journal of Educational Innovation and Public Health, 2026)
Background: Knee osteoarthritis is a degenerative joint disease that often occurs in the geriatric population and causes pain, limited movement, and decreased function. In advanced conditions, management is carried out with Total Knee Replacement (TKR). However, post-surgery patients still experience functional limitations so that physiotherapy intervention is needed. Objective: To determine the effectiveness of static bicycle and quadriceps strengthening exercises on pain, range of motion, muscle strength, functional mobility, and quality of life in post-TKR patients. Methods: This study used a case study design in one patient with post-TKR dextra et causa bilateral knee osteoarthritis. The intervention was given for 3 weeks with a frequency of 2 times per week. Evaluation was carried out using the Numeric Rating Scale (NRS), goniometer, Manual Muscle Testing (MMT), Timed Up and Go Test (TUG), and the Knee Osteoarthritis Outcome Score (KOOS). Results: Results showed a decrease in motion pain from NRS 6 to 4 and stationary pain from 3 to 2. Knee range of motion increased from 75° to 90° of flexion and from -5° to 0° of extension. Muscle strength increased from MMT 3 to 4 in the quadriceps muscle. Functional mobility also improved, with TUG time decreasing from 22 seconds to 18 seconds. However, the KOOS score remained relatively unchanged at 38.84. Conclusion: Static bicycle and quadriceps strengthening exercises were effective in reducing pain, increasing ROM, muscle strength, and functional mobility in post-TKR patients. However, the improvement in quality of life as measured by the KOOS was not significant, requiring a longer rehabilitation period.